2017
DOI: 10.5539/jel.v6n2p220
|View full text |Cite
|
Sign up to set email alerts
|

Metaphoric Perception of Gifted Students about Physical Education Course and Physical Education Teachers

Abstract: It is to determine the perception of the gifted students who participate to "Science and Art Center" about "Physical Education Course" and "Physical Education Teachers" via metaphors. The working group of the research consists of 48 students who participate Science and Art Center in 2014-2015 school years. Among the purposive sampling methods, criterion sampling method is used in choosing the working group. In the research, among the qualitative research approaches, phenomenological design is used. The data is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Metaphor can be expressed as using another concept while explaining one concept or benefiting from the features of that concept. According to these explanations, in its most general definition, the metaphor provides the opportunity to tell the unknown through the known and to make the phenomenon known from the analogies of a phenomenon, and to see a phenomenon as another phenomenon (Yilmaz, Esenturk, Demir & Ilhan, 2017;Toptaş & Gözel, 2018). Over the past decade, research on the development of figurative language has expanded considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Metaphor can be expressed as using another concept while explaining one concept or benefiting from the features of that concept. According to these explanations, in its most general definition, the metaphor provides the opportunity to tell the unknown through the known and to make the phenomenon known from the analogies of a phenomenon, and to see a phenomenon as another phenomenon (Yilmaz, Esenturk, Demir & Ilhan, 2017;Toptaş & Gözel, 2018). Over the past decade, research on the development of figurative language has expanded considerably.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen in recent years that metaphor studies are frequently conducted for determining perceptions of participants on a topic or a subject (Akgün, 2016;Aktamış and Dönmez, 2016;Derman, 2014;Durukan, Hacıoğlu and Dönmez-Usta, 2016;Kahyaoğlu, 2015;Kaya, 2014;Paliç-Şadoğlu and Uzun, 2014;Saban, 2009;Yılmaz, Esentürk, Tekkurşun-Demir and İlhan, 2017). A metaphor may be defined as an explanation of an event, concept or phenomenon by likening it to another event, concept or phenomenon (Oxford, Tomlinson, Barcelos, Harrington, Lavine, Saleh and Longhini, 1998;Aslan, 2013;Aydın and Eser Ünaldı, 2010;Saban, 2008).…”
Section: Data Collection Toolmentioning
confidence: 99%
“…As a result of the literature review on metaphors, researches on sports have been found. (Segrave, 2000;Cudd, 2007;Özsoy, 2011;Karasahinoglu & Ilhan, 2015;Kesic & Muhic, 2013;Koç et al, 2015;Yilmaz et al, 2017). This study differs from others in that it tries to measure the metaphorical perceptions of sport managers.…”
Section: Introductionmentioning
confidence: 96%